Response to Groarke : Figuring Sound - Eckstein, Justin (Informal Logic, 2018)
This essay notes the tendency to reduce sound to a cause of something else. Such a position constrains theory construction to only cause and effect schemes. I argue that we should expand our understanding of sound to include what I term sound figures, which acknowledge that sounds can represent the world. I conclude by offering an understanding of sound fig-ures tied to their resonance.